Reverse-phase High-performance Liquid Chromatography Estimation of Methotrexate and Tretinoin in Bulk and Pharmaceutical Dosage Forms: Reverse-phase High-performance Liquid Chromatography Estimation of Methotrexate and Tretinoin in Bulk and Pharmaceutical Dosage Forms - Agrawal, Ashish (International Journal of Pharmaceutical & Biological Archive, 2019)
A simple, sensitive, and selective reverse-phase high-performance liquid chromatography (RP-HPLC) method with for the estimation of methotrexate (MTX) and tretinoin in pharmaceutical formulation and in spiked plasma developed and validate in the present work. Chromatographic separation of drug is performed with a 250 mm Ã— 4.6 mm, 5 Î¼m diameter particles RP C-18 column, and the mobile phase consisted of a mixture of Acetonitrile (ACN):buffer (85:15, v/v). Isocratic elution at a flow rate of 1 ml/min with ultraviolet detection at 340 nm at ambient temperature is used in this method. The proposed RP-HPLC method is successfully applied for the determination of MTX and tretinoin in pharmaceutical preparation and spiked plasma samples. The validation studies are carried out and itâ€™s fulfilling ICH requirements. The method is found to be specific, linear, precise (including both intra- and inter-day precision), accurate, and robust. This proposed method may represent a valuable aid in the laboratory monitoring of the toxicity of anticancer chemotherapy.